Stressors from Caregiving for Cardiovascular Diseases: Insights from a Community-based Cross-sectional Study in New Delhi - Kaur, Prabhjeet; Goel, Manish Kumar; Prasuna, Josyula Gnana (Indian Journal of Community Health, 2024)
Background: Providing care for chronic conditions at home imposes various responsibilities on caregivers, affecting financial, physical, emotional, and social domains. Over time, these responsibilities can accumulate and become significant stressors. Aims & Objectives: The study aims to assess the magnitude, factors and reasons of stressors faced by caregivers of cardiovascular diseases (CVD). Material and Methods: Community-based cross-sectional study was conducted in Delhi. A sample of 384 households was obtained through systematic random sampling. The sampling unit was the household, and the study units were the primary caregivers of individuals with cardiovascular diseases. Results: Among 384 caregivers, 223 (58%) were female, and 50.3% were spouses of the patients. The magnitude of stressors ranged from 79.4% to 90.4%. The main stressors identified were economic burden (70.8%), knowledge about the medical condition (67.7%), and changed patient behavior (65.6%). Significant associations were found between stressors and certain socio-demographic factors (such as occupation and relationship to the patient) as well as disease-related factors (such as duration of caregiving, regularity of treatment, patient condition, ADL impairment, and multimorbidity of CVD). Conclusion: These results highlight the dyadic relationship between patients and caregivers, emphasizing that caregivers are a high-risk group that also requires attention and support.